Effectiveness of a school‐ and community‐based academic asthma health education program on use of effective asthma self‐care behaviors in older school‐age students. Issue 1 (30th November 2014) - Kintner, Eileen K.; Cook, Gwendolyn; Marti, C. Nathan; Allen, April; Stoddard, Debbie; Harmon, Phyllis; Gomes, Melissa; Meeder, Linda; Van Egeren, Laurie A.
Abstract Purpose The purpose was to evaluate the effectiveness of Staying Healthy–Asthma Responsible & Prepared, an academic asthma health education and counseling program, on fostering the use of effective asthma self‐care behaviors. Design and Methods This was a phase III, two‐group, cluster randomized, single‐blinded, longitudinal design‐guided study. Caregivers of 205 fourth‐ and fifth‐grade students completed the asthma health behaviors survey at preintervention, and 1, 12, and 24 months postintervention. Analysis involved multilevel modeling. Results All students demonstrated improvement in episode management, risk reduction/prevention, and health promotion behaviors; Staying Healthy–Asthma Responsible & Prepared students demonstrated increased improvement in episode management and risk reduction/prevention behaviors. Practice Implications Working with schoolteachers, nurses can improve the use of effective asthma self‐care behaviors.